Investigating decadal changes in persistent organic pollutants in Scottish grey seal pups. (6th September 2019) - Robinson, Kelly J.; Hall, Ailsa J.; Scholl, Georges; Debier, Cathy; Thomé, Jean‐Pierre; Eppe, Gauthier; Adam, Catherine; Bennett, Kimberley A.
Abstract: Persistent organic pollutants (POPs) remain a risk to marine ecosystem health. POPs accumulate in fat tissue and are biomagnified up through food webs, generating high concentrations in apex predators, including marine mammals. Seals are thus often cited as sentinels of marine environment POP levels. Measuring changes across decadal timescales in these animals is key to understanding the effectiveness of regulations controlling POPs, predicting health, population, and ecosystem level impacts, and informing conservation and management strategies. Information on recent changes in legacy POPs in seals is relatively sparse, however, and datasets are not always continuous in the absence of dedicated POP monitoring programmes. Here, POP concentrations in the blubber of weaned grey seal pups from the Isle of May, Scotland, were compared between studies investigating POP impacts on survival and energy balance in 2002, and in 2015–17. By 2017, the total dioxin‐like polychlorinated biphenyls (ΣDL‐CBs) and the total non‐dioxin‐like polychlorinated biphenyls (ΣNDL‐CBs) had decreased to ~75% of 2002 levels. The organochlorine pesticides (OCPs), dichlorodiphenyltrichoroethane (ΣDDT), dichlorodiphenyldichloroethylene (DDE), and dichlorodiphenyldichoroethane (DDD), and some CB congeners, did not fall over the 15‐year period; however, the power to detect small changes at low concentrations was limited. High DDE and a lack of change in DDD are likely to reflect the low excretion of DDT metabolites, rather than recent exposure. The limited change in many POPs over 15 years suggest that risks remain for energy balance, endocrine status, and immune function in grey seal pups, with contingent effects on conservation and management objectives for this species. These data highlight the need for long‐term datasets and parity in sampling and analytical methods to evaluate continuing impacts of POPs in grey seals and on marine ecosystems more widely.